Biogeography of algae and invertebrates from wave-exposed rocky intertidal habitats along the Atlantic coast of Nova Scotia (Canada): Latitudinal and interannual patterns and possible underlying drivers - Scrosati, Ricardo A.; Freeman, Matthew J.; Ellrich, Julius A.; Petzold, Willy (Frontiers in Marine Science, 2022)
Biogeographic studies aim to understand species distributions and are becoming increasingly relevant to establish baselines to monitor ecological change. The NW Atlantic coast hosts a cold-temperate biota, although knowledge about its biogeography is patchy. This study documents for the first time biogeographic variation at mid-to-high intertidal elevations in wave-exposed rocky intertidal habitats along the open Atlantic coast of Nova Scotia (Canada), a hydrographically distinct subregion of this cold-temperate region. For this goal, we measured the summer abundance of algae and invertebrates at the same nine locations over four consecutive years (2014 to 2017) spanning 415 km of coastline, which allowed us to examine latitudinal and interannual patterns. In addition, we looked for mensurative evidence on possible drivers underlying these patterns, focusing on sea surface temperature, daily maximum and minimum temperature (which often happen at low tides at thus differ from sea surface temperature), pelagic food supply for intertidal filter-feeders (phytoplankton abundance and particulate organic carbon), drift sea ice during the cold season (which can cause intertidal disturbance), and species associations. Our field surveys revealed that northern locations can be severely disturbed by ice scour when drift ice is abundant and, while biological recolonization occurs over the years, it differs in pace among locations. Southern locations, instead, did not experience ice scour during our study and, thus, generally exhibited a higher species richness and abundance than northern locations. Multivariate analyses indicated that the aforementioned expressions of temperature and pelagic food supply explained together 32–55% of the variation in alongshore biogeographic pattern, depending on the year. Species association analyses suggest that algal foundation species (generally more abundant at southern locations) contribute to increase location-wise species richness. Mensurative evidence for bottom-up forcing in seaweed–herbivore and filter-feeder–predator systems differed greatly among years. Overall, in addition to its inherent value to advance NW Atlantic intertidal biogeography, our species distribution database should be valuable to assess ecological change decades into the future as climate change and other anthropogenic influences unfold.